Advanced glaucoma at presentation is associated with poor follow-up among glaucoma patients attending a tertiary eye facility in Southern Nigeria. (4th May 2018) - Momoh, Rita Omoso; Bunce, Catey; Oko-oboh, Gregrey Agbonvihele; Gilbert, Clare E.
ABSTRACT: Purpose : Globally, particularly in Africa, poor compliance with medication is a major problem in glaucoma management but little is known about follow-up rates among African glaucoma patients. The aim of this study was to determine rates of follow-up among glaucoma patients attending a tertiary hospital in southern Nigeria and investigate predictors of poor follow-up. Methods : Data were extracted from medical records of new glaucoma patients who attended the hospital between June 2011 and May 2013. Socio-demographic and clinical parameters (visual acuity; stage of glaucoma) recorded at diagnosis were extracted using a pre-tested form. Follow-up was defined as good if they had attended within 9 months of the study date, inadequate when the last follow-up was more than 9 months and failed if they did not attend any follow-up or the most recent visit was more than 14 months from the study date. Univariate and multivariable analyses were undertaken to explore predictors of poor follow-up (inadequate plus failed). Results : Three hundred forty-eight patients were recruited, 54% were male and the mean age was 52.7 (range 16–88) years. Follow-up was as follows: good 28.4%, inadequate 46.6%, failed 25%. Overall, 71.6% had poor follow-up. Independent predictors of poor follow-up were poorer visual acuity (OR 3.85, 95% confidence interval (CI) 1.25–11.80 for visual impairment; OR 4.11, 95% CI 1.32–12.81 for blind) and end-stage glaucoma (OR 3.55 (1.31–9.62), p = 0.01). Conclusion : Enhanced counselling of patients with moderate to advanced glaucoma and visual impairment is required to improve follow-up and hence glaucoma management.